On the topology of the complement of a singular plane curve in the classiﬁcation of singular holomorphic foliations of codimension one - Neciosup Puican, Hernán (2023)
In this article, we study the role of the fundamental group of the complement of an aﬃne plane curve in the analytic classiﬁcation of singular codimension-one foliations in (C3, 0). We focus on obtaining an adequate representation of the fundamental group of a particular aﬃne plane curve complement, using braid monodromy and the Zariski-Van Kampen method. The image of this group, under the holonomy representation of the foliation, is known as the holonomy group of the foliation and the analytic conjugacy of these groups is equivalent to the analytic classiﬁcation of almost homogeneous cuspidal singular holomorphic foliations of admissible type on (C3, 0) [6].